DISHARMONISASI PROBLEM PENGELOLAAN SUMBER DAYA ALAM DI KABUPATEN KOTABARU - GUSTI MUZAINAH (Syariah: Jurnal Hukum dan Pemikiran, 2015)
This paper discusses the rules that con?ict with the higher, so the local regulations must be canceled. If the local law has been withdrawn, the local laws cannot be enforced and cannot be guided due to invalid. On the contrary, if the local legislation has not been canceled, then the local regulations have binding force or valid until cancellation. The urgency of norms con?ict resolution of that theory, based on the deepest layer of law that is the legal philosophy in mining activities in forest areas is precisely the Forestry Act rests the preservation of forests while the regency government was grounded in economic interests.